Disruptive innovation in the classroom - Singapore Management University (Institutional Knowledge at Singapore Management University, 2013)
Disruptive innovation, as described on the website of the man who coined the term, Clayton Christensen, is "a process by which a product or service takes root initially in simple applications at the bottom of a market and then relentlessly moves up market, eventually displacing established competitors". Prominent examples include how the personal computer (disruptor) displaced the mainframe computer (disruptee), cellular phones displacing fixed line telephony, and community colleges eating into the market share of four-year colleges.